Engineering Glucose-to-Glycerol Pathway in Klebsiella pneumoniae and Boosting 3-Hydroxypropionic Acid Production Through CRISPR Interference - Liu, Hexin; Zhao, Peng; Tian, Pingfang (Frontiers in Bioengineering and Biotechnology, 2022)
The recent decline of the international biodiesel industry has led to decreased production and therefore increased the price of glycerol, which is a major by-product of biodiesel but a substrate for production of 3-hydroxypropionic acid (3-HP), that is, glycerol as a feedstock has no advantage over glucose in price. Hence, we engineered glucose to the glycerol pathway and improved 3-HP production by CRISPR interference (CRISPRi). To begin with, we cloned the genes encoding glycerol 3-phosphate dehydrogenase (gpd1) and glycerol 3-phosphatase (gpp2) from Saccharomyces cerevisiae, which jointly catalyze glucose into glycerol. The genes gpd1 and gpp2 were co-expressed in K. pneumoniae with the dCas9 gene integrated in genome, and this recombinant strain produced 2 g/L glycerol in the shake flask. To minimize the glucose consumption by competing pathways including the EMP pathway, glycerol oxidation pathway, and by-products pathways, we developed an CRISPRi system in aforementioned recombinant K. pneumoniae strain to inhibit the expression of the glyceraldehyde-3-phosphate dehydrogenase gene (gapA) and 2,3-butanediol production gene (budA), resulting in a bi-functional strain harboring both glucose-to-glycerol pathway and CRISPRi system. Reverse transcription and quantitative PCR (RT-qPCR) results showed that this engineered CRISPRi system transcriptionally inhibited gapA and budA by 82% and 24%, respectively. In shake flask cultivation, this bi-functional strain produced 2.8 g/L glycerol using glucose as the carbon source, which was 46.6% increase compared to the strain without the engineered CRISPRi system. Moreover, this bi-functional strain produced 0.78 g/L 3-HP using glucose as the sole carbon source. In fed-batch cultivation, this bi-functional strain produced 1.77 g/L 3-HP. This study provides insights for co-utilization of distinct carbon sources.